Factors associated with fluctuations in repeated measurements of intraocular pressure using the Goldmann applanation tonometer in Japanese patients with primary open-angle glaucoma - Yaoeda, Kiyoshi (Clin Ophthalmol, 2018)
PURPOSE: The aim of this study was to determine whether fluctuations in intraocular pressure (IOP) occur as a result of the order of IOP measurements or successive IOP measurements in patients with glaucoma and, if so, identify the factors causing these fluctuations. PATIENTS AND METHODS: Four hundred twenty-eight eyes of 214 Japanese patients with primary open-angle glaucoma (POAG) were enrolled. Patients treated with beta-blockers or prostaglandin analogs alone were included. Additionally, in the IOP measurements by noncontact tonometer, the same cases of IOP of the right and left eyes prior to this study were included in this study. Four successive IOP measurements were carried out using a Goldmann applanation tonometer as follows: IOP was measured in the first eye (right or left) and then in the fellow eye and IOP was again measured in the first eye and then in the fellow eye. Repeated-measures analysis of variance was used to test the differences in IOP between successive measurements. Generalized linear mixed models were used to test differences in IOP measurements between the right and the left eyes on repeated applanation tonometry and according to the order of measurement. Conditional binomial logistic regression analysis was used to identify factors associated with fluctuating repeated applanation tonometry measurements. A P-value of <0.05 was considered statistically significant. RESULTS: IOP values decreased significantly according to the number of measurements (13.8–13.0; P<0.001–0.036, respectively). There was no significant difference in IOP measurements between the right and left eyes. The first IOP measurement was significantly higher than the fourth measurement (P=0.038); however, there was no significant difference between other combinations. The use of a prostaglandin analog was the only significant contributor to fluctuating IOP measurements (P=0.002). CONCLUSION: IOP measured in the first eye, either right or left, was higher than that measured in the fellow eye in Japanese patients with POAG. The use of a prostaglandin analog may be associated with fluctuating IOP on repeated applanation tonometry.